Bilateral agreement for academic years 2008/2013 Lifelong Learning Programme Erasmus - between programme countries – Università degli Studi di Padova and Universidade Lusíada de Lisboa - Universidade Lusíada de Lisboa (2016)
- Cooperate in the activities established by the European Commission in the frame of the new Lifelong Learning Programme 2007-2013; - Subject area: Law; Political Science.